MULTIMEDIA APPLICATION BERBASIS GAME EDUKASI - annisa putri; ade wisandra (JURTEII: Jurnal Teknologi Informasi, 2025)
This study aims to identify and analyze the development trends of multimediaapplications based on educational games, including the platforms used, research modelsapplied, and the outcomes of their implementation in learning activities. The researchmethod employed is a Systematic Literature Review (SLR) conducted through systematicstages of planning, identification, selection, analysis, and synthesis of relevant literature.The data consist of 15 national journal articles published between 2020 and 2025 thatfocus on the development of multimedia-based educational games. The most commonlyused research models identified in the reviewed studies include Research andDevelopment (R&D), ADDIE, and the Multimedia Development Life Cycle (MDLC). Theresults indicate that multimedia applications based on educational games consistentlyenhance learning motivation, interactivity, conceptual understanding, and students’learning outcomes across various educational levels. Furthermore, the findings revealthat Android platforms and interactive multimedia dominate current development trends,along with alignment to the Independent Curriculum (Kurikulum Merdeka). Therefore,multimedia applications based on educational games are considered effective andfeasible as innovative learning media to support 21st-century education.